Futuro presente. Alcune considerazioni sul contesto programmatico di Blade Runner 2049 - Pivetta, Michelangelo (Firenze Architettura, 2018)
The recent sequel to Ridley Scott’s original work proposes some further insights into the field of dystopian imagery in the vision of a close society. The enigma, suggested, lies in the evident relationships between script and set design, between real and unreal, prediction and reality, dystopian and utopian, where architecture is not only an essential background, but a leading actor.